2014
DOI: 10.1158/1541-7786.mcr-13-0351
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Independent Gene Expression Mediated by SOX9 Promotes Aggressive Pancreatic Tumor Biology

Abstract: Pancreatic cancer aggressiveness is characterized by its high capacity for local invasion, ability to promote angiogenesis, and potential to metastasize. Hypoxia is known to represent a crucial step in the development of aggressive malignant features of many human cancers. However, micrometastatic tumors are not typically subjected to hypoxic events during early stages of dissemination; therefore, it is unclear how these tumors are able to maintain their aggressive phenotype. Thus, the identification of regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…As the promoters of HNF1A upregulated genes were enriched for transcription factor known to play roles in PDA including GATA (likely GATA5 or GATA6) (Roe et al, 2017; Martinelli et al, 2017; Zhong et al, 2011), PDX1 (Roy et al, 2016), and SOX9 (Camaj et al, 2014; Kopp et al, 2012; Tsuda et al, 2018), it is possible that HNF1A may work in concert with other transcription factors to elicit its full oncogenic function in PDA. A similar interaction between the transcription factors Foxa1 and Gata5 was recently described in driving metastasis in murine models of PDA (Roe et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As the promoters of HNF1A upregulated genes were enriched for transcription factor known to play roles in PDA including GATA (likely GATA5 or GATA6) (Roe et al, 2017; Martinelli et al, 2017; Zhong et al, 2011), PDX1 (Roy et al, 2016), and SOX9 (Camaj et al, 2014; Kopp et al, 2012; Tsuda et al, 2018), it is possible that HNF1A may work in concert with other transcription factors to elicit its full oncogenic function in PDA. A similar interaction between the transcription factors Foxa1 and Gata5 was recently described in driving metastasis in murine models of PDA (Roe et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a subpopulation of CSCs expressing CD133 and CXCR4 in invasive pancreatic tumors was found to be the determinant of metastasis (Hermann et al, 2007). While HIF-1α is known to be a major factor contributing to CXCR4 expression in pancreatic and other cancers, recent studies in pancreatic cancer cells and tumors demonstrated that transcription factors such as SOX9 upregulate CXCR4 expression independently of HIF-1α, which may have consequences not only for pancreatic cancer but also for other cancers such as SCLC where SOX transcription factors are known to be overexpressed (Camaj et al, 2014). CXCR4 antagonist AMD3100 significantly inhibited the proliferation, migration, and invasion of pancreatic cancer cells (Gao, Wang, Wu, Zhao, & Hu, 2010).…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
“…Hypoxia contributes to disease progression and promotes tumor growth and invasion, and clinical studies have shown that high levels of hypoxia directly correlate with a poor prognosis in pancreatic cancer (7). The observed correlation between tumor hypoxia and patient prognosis is ascribed to therapeutic failure and hypoxiainduced pro-metastatic potential, as several studies have shown that hypoxia stimulates a more invasive, metastatic phenotype via multiple mechanisms (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%